2017
DOI: 10.1111/jog.13284
|View full text |Cite
|
Sign up to set email alerts
|

Amniotic fluid embolism: Pathophysiology from the perspective of pathology

Abstract: Amniotic fluid embolism (AFE) is recognized as a type of syndrome characterized by the abrupt onset of hypoxia, hypotension, seizures, or disseminated intravascular coagulopathy (DIC), occurring during labor, delivery, or immediately postpartum, caused by the inflow of amniotic components into the maternal circulation. AFE is a rare condition but one of the most serious obstetrical complications, resulting in a high mortality rate among pregnant women. Despite earlier recognition and intensive critical managem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 50 publications
2
37
0
5
Order By: Relevance
“…However, if the fibrinogen level is less than 1.5 g/L, the earlier replacement of blood coagulation factors is recommended according to the Japanese guidelines ( 13 ). Based on our previous report ( 26 ), earlier interventions with plasma-derived blood products might further inhibit an anaphylactoid reaction in the lungs and uterus ( 27 , 28 ) effectively. On the other hand, repeated screening of blood coagulability is recommended when fibrinogen levels are maintained at more than 1.5 g/L, because patients may be at risk of further deteriorations in blood coagulation.…”
Section: Discussionmentioning
confidence: 94%
“…However, if the fibrinogen level is less than 1.5 g/L, the earlier replacement of blood coagulation factors is recommended according to the Japanese guidelines ( 13 ). Based on our previous report ( 26 ), earlier interventions with plasma-derived blood products might further inhibit an anaphylactoid reaction in the lungs and uterus ( 27 , 28 ) effectively. On the other hand, repeated screening of blood coagulability is recommended when fibrinogen levels are maintained at more than 1.5 g/L, because patients may be at risk of further deteriorations in blood coagulation.…”
Section: Discussionmentioning
confidence: 94%
“…Over the years, inconsistencies in laboratory evidence and autopsy findings were unable to validate this theory. In 1995, Clark et al demonstrated that the etiology of AFE was immunologically mediated by activation of the complement cascade and mast cell degranulation; coining the term "Anaphylactoid Syndrome of Pregnancy" [6].…”
Section: Discussionmentioning
confidence: 99%
“…The common histopathological finding among these women was the presence of amniotic fluid debris in the pulmonary vasculature [1]. Therefore, the historical hypothesis was based on an obstruction of the pulmonary arteries from amniotic fluid or fetal debris [1,3]. Medical advancements in the 1980s allowed for more frequent use of the pulmonary artery catheter to obtain arterial histologic specimens from living patients [1].…”
Section: Pathophysiologymentioning
confidence: 99%
“…The second and more commonly accepted theory is that AFE results from a complex sequence of reactions involving an abnormal activation of proinflammatory mediators in the host leading to an immunologic response [1][2][3][4][5][6][7]. This response is similar to the systemic inflammatory response syndrome (SIRS).…”
Section: Pathophysiologymentioning
confidence: 99%